Implementasi Strategi Kewirausahaan Dalam Konteks Pendidikan: Mewujudkan Dinamika Kompetitif di Lembaga Pendidikan - Hesti Kusumaningrum; Akbar Dwi Dharmawan; Deni Sahroni; Zakaria Safardi (Student Scientific Creativity Journal, 2024)
This research utilizes the library research method, which involves the use of library sources as the basis for collecting research data. These sources include books and scholarly journals relevant to the topic under investigation. The purpose of this research is to know and understand the implementation of entrepreneurial strategies in the context of education as a whole. This research discusses the implementation of entrepreneurial strategies in the context of education and how it can realize competitive dynamics in educational institutions. In this challenging era, educational institutions are required to not only produce academically qualified graduates, but also have the readiness to face the rapidly changing business world. The data collected was carefully analyzed to support the arguments built in this study. The findings of this study illustrate that the implementation of entrepreneurial strategies in education can create a dynamic and competitive atmosphere in educational institutions. This can be realized through building soft skills or entrepreneurial character, developing quality educational programs, and implementing effective marketing strategies. The implications of this research provide an important contribution in enriching the understanding of the importance of entrepreneurship integration in an educational context and how it can produce graduates who are ready to compete in an increasingly complex business world.